Dictators and democracy in African development : the political economy of good governance in Nigeria - LeVan, A. Carl (Cambridge University Press, 2014)
This book argues that the structure of the policy-making process in Nigeria explains variations in government performance better than other commonly cited factors.
Keywords: Nigeria -- Politics and government.; Dictatorship -- Nigeria.; Democracy -- Nigeria.; Economic development -- Political aspects -- Nigeria.; Nigeria -- Economic conditions.; Nigeria -- Politique et gouvernement.; Dictature -- Nigeria.; Développement économique -- Aspect politique -- Nigeria.; Nigeria -- Conditions économiques.; POLITICAL SCIENCE -- Essays.; POLITICAL SCIENCE -- Government -- General.; POLITICAL SCIENCE -- Government -- National.; POLITICAL SCIENCE -- Reference.; Democracy; Dictatorship; Economic development -- Political aspects; Economic history; Politics and government; Nigeria; Agency-Theorie; Demokratie; Diktatur; Machtmissbrauch